ANALISIS PENGARUH BUDAYA ORGANISASI DAN TIPE KEPRIBADIAN TERHADAP KUALITAS LAYANAN MELALUI ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) (STUDI PADAPT. BANK BUKOPIN TBK (PERSERO) JEMBER) - Puspita Anggarini (RELASI : JURNAL EKONOMI, 2015)
Companies, especially Bank, requires strategy and characteristics in order to achieve success. One of the efforts to achieve the success of the company is to provide the best quality service. This study aims to examine the influence of organizational culture Testing (X1) on the quality of service (Y2), the influence of personality type (X2) on the quality of service, the influence of organizational culture on Organizational citizen behavior (OCB) (Y1), the influence of personality type on OCB, and OCB influence on the quality of service of employees of PT. Bank Bukopin Jember branch. Selected 102 respondents using census technique to fill in a questionnaire study. And the results of the questionnaire data processed by data analysis techniques Structural Equation Modeling (SEM). The result shows that the organizational culture significantly influence OCB, the personality type significantly influence OCB, the organizational culture significantly influence the quality of service, personality types have a significant effect on the quality of service, and OCB is one of significant effect on service quality.